Effect of Lignin and other Biopolymers on Hyperlipidemia and Gut Microbiota - Abu-Omar, Amira; Hasan, Eliza; Gil-Chávez, Joana; Athamneh, Tamara; Abazid, Husam; Gurikov, Pavel; Al-Najjar, Mohammad A. A. (Jordan Journal of Pharmaceutical Sciences, 2025)
So far, dietary fibers such as lignin, cellulose, pectin, guar gum, and psyllium have been well-studied for their preventive and therapeutical potential using animal and human models, especially for their beneficial effects on chronic metabolic conditions like dyslipidemia and related disorders. Dyslipidemia is a dangerous metabolic disorder related to hypercholesterolemia, coronary artery disease, and coronary heart disease. Earlier research has demonstrated that these dietary fibers can lower high serum lipid levels through different mechanisms. One of the most important mechanisms is the modification of gut microbiota. Increasing the abundance of lactic acid bacteria (LAB), which can metabolize different dietary fibers like lignin, may potentially reduce the cholesterol level. This review aims to provide useful insights and comprehensive discussions about current knowledge related to the properties, and the effects of dietary fibers mainly lignin in controlling hyperlipidemia and their effects on gut microbiota. Google Scholar, Research Gate, and Scopus are the search engines exploited to collect data by using lignin, biopolymers, gut microbiota, and hyperlipidemia as search terms.